1997
DOI: 10.1103/physrevlett.79.1070
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Feature in the Pseudogap of Quasicrystals Detected by NMR

Abstract: The 27 Al and 63 Cu spin-lattice relaxation rates were found to contain a large T 2 term over a wide temperature range below 400 K in several thermodynamically stable quasicrystalline alloys, including i-AlCuRu, i-AlPdRe, i-AlCuFe, and the crystalline approximant phase a-AlMnSi. The relaxation mechanism is proven to be electronic in origin. Such nonlinear temperature dependence is shown to be a clear signature of sharp features in the density of states at the Fermi level. The estimated width of this sharp feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 22 publications
(31 reference statements)
0
21
3
Order By: Relevance
“…5 However we found no evidence for a temperature dependence to K m , as has been found in some systems 37,38 for which narrow pseudogap features dominate near ε F . Thus from this standpoint Fe 2 Al 5 behaves as an ordinary metal.…”
Section: Discussioncontrasting
confidence: 43%
“…5 However we found no evidence for a temperature dependence to K m , as has been found in some systems 37,38 for which narrow pseudogap features dominate near ε F . Thus from this standpoint Fe 2 Al 5 behaves as an ordinary metal.…”
Section: Discussioncontrasting
confidence: 43%
“…It is suggested that spikes could be artifacts of the calculation 26,27 or only specific to small periodic approximants 24,28,29 ͑APP's͒. On the other hand, there is experimental evidence 30,31 for significant spectral structures around the Fermi energy down to a few 10 meV. Measurements 9,10,32,33 of the temperature-dependent conductivity and the thermopower indicate also the presence of narrow pseudogaps ͑width ϳ0.1-0.2 eV͒ in the spectral conductivity.…”
Section: Introductionmentioning
confidence: 96%
“…1͒ agrees well with the experimental results obtained from tunneling and point contact spectroscopy measurements, where the presence of a dip feature of small width ͑20-60 meV͒, superimposed onto a broad ͑0.5-1 eV͒ asymmetric pseudogap, has been reported. 23,[31][32][33] Thus, Eq. ͑2͒ satisfactorily describes the electronic structure of these alloys in terms of a wide Lorentzian peak ͑related to the Fermi surface-Brillouin zone interaction͒ plus a narrow Lorentzian peak ͑related to sp-d hybridization effects͒.…”
Section: ͑2͒mentioning
confidence: 99%